The Great Depression and the Friedman-Schwartz hypothesis - Lawrence Christiano; Roberto Motto; Massimo Rostagno (European Central Bank (ECB), 2004)
We evaluate the Friedman-Schwartz hypothesis that a more accommodative monetary policy could have greatly reduced the severity of the Great Depression. To do this, we first estimate a dynamic, general equilibrium model using data from the 1920s and 1930s. Although the model includes eight shocks, the story it tells about the Great Depression turns out to be a simple and familiar one. The contraction phase was primarily a consequence of a shock that induced a shift away from privately intermediated liabilities, such as demand deposits and liabilities that resemble equity, and towards currency. The slowness of the recovery from the Depression was due to a shock that increased the market power of workers. We identify a monetary base rule which responds only to the money demand shocks in the model. We solve the model with this counterfactual monetary policy rule. We then simulate the dynamic response of this model to all the estimated shocks. Based on the model analysis, we conclude that if the counterfactual policy rule had been in place in the 1930s, the Great Depression would have been relatively mild.
Keywords: E31; E40; E51; E52; E58; N12; 330; deflation; General Equilibrium; lower bound; shocks